2018
DOI: 10.1097/brs.0000000000002510
|View full text |Cite
|
Sign up to set email alerts
|

Descriptive Analysis of State and Federal Spine Surgery Malpractice Litigation in the United States

Abstract: 4.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
83
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 52 publications
(86 citation statements)
references
References 45 publications
3
83
0
Order By: Relevance
“…29 Factors increasing the risk of litigation in this subspecialty range from a lack of professionalism to poorly informed consent. 37 Interestingly, we noted that MTCs in spine procedures were lower than those in the other subspecialties.…”
Section: Discussionmentioning
confidence: 75%
“…29 Factors increasing the risk of litigation in this subspecialty range from a lack of professionalism to poorly informed consent. 37 Interestingly, we noted that MTCs in spine procedures were lower than those in the other subspecialties.…”
Section: Discussionmentioning
confidence: 75%
“…28 A study from the United States found that a lack of informed consent was the second most common reason for malpractice litigation among patients undergoing brain tumor surgery (24.4% of cases), behind a failure to diagnose (28.0% of cases). 20 Other studies determined that a lack of informed consent was the third most common reason for litigation, 11,13,14 while others found that litigation on grounds of lack of informed consent was less common. 12,26 One study found that a lack of informed consent was implicated in cranial cases more often than in spinal cases.…”
Section: Medicolegal Implications Of Informed Consentmentioning
confidence: 99%
“…12,26 One study found that a lack of informed consent was implicated in cranial cases more often than in spinal cases. 13 Median or mean payments were greater for plaintiff verdicts than for the settlements for spine surgery malpractice cases, 11,14 whereas payments for settlements were greater than those for plaintiff verdicts for endoscopic sinus surgery. 12 Four studies examined spine surgery.…”
Section: Medicolegal Implications Of Informed Consentmentioning
confidence: 99%
“…The results of a retrospective analysis of spine-related malpractice litigation cases in the US are in line with these findings, showing that 37.7% of all spine surgery malpractice cases are related to decompressions. 17 Thomas et al analyzed 343 cases filed between 1985 and 2015 that were related to medical malpractice and neurosurgery by using a comprehensive database for legal information in the US. 18 Among these cases, most were related to spine procedures (58.0%), which is in line with the experiences of our respondents.…”
Section: Comparison With Other Studiesmentioning
confidence: 99%